The 5T approach in asthma: Triple Therapy Targeting Treatable Traits. (August 2022) - Cazzola, Mario; Braido, Fulvio; Calzetta, Luigino; Matera, Maria Gabriella; Piraino, Alessio; Rogliani, Paola; Scichilone, Nicola
Abstract: Using a therapeutic strategy that is free from traditional diagnostic labels and based on the identification of "treatable traits" (TTs), which are influential in clinical presentations in each patient, might overcome the difficulties in identifying and validating asthma phenotypes and endotypes. Growing evidence is documenting the importance of using the triple therapy with ICS, LABA, and LAMAs in a single inhaler (SITT) in cases of asthma not controlled by ICS/LABA and in the prevention of exacerbations. The identification of TTs may overcome the possibility of using SITT without considering the specific needs of the patient. In effect, it allows a treatment strategy that is closer to the precision strategy now widely advocated for the management of patients with asthma. There are different TTs in asthma that may benefit from treatment with SITT, regardless of guideline recommendations. The airflow limitation and small airway dysfunction are key TTs that are present in different phenotypes/endotypes, do not depend on the degree of T2 inflammation, and respond better than other treatments to SITT. We suggest that the 5T (Triple Therapy Targeting Treatable Traits) approach should be applied to the full spectrum of asthma, not just severe asthma, and, consequently, SITT should begin earlier than currently recommended. Highlights: A systematic approach to addressing treatable traits (TT) in asthma is clinically effective. Eosinophilic airway inflammation, airflow limitation, and tendency to exacerbations are TTs present in many of the clinical phenotypes of asthma, albeit with different burdens. Further pulmonary TTs, such as mucus hypersecretion, oxygen desaturation, dyspnea, neutrophilic airway inflammation and small airway involvement, extrapulmonary traits, behavioral traits, and risk factors also deserve attention. Identifying TTs, which should be applied to the whole spectrum of asthma, can allow a therapeutic strategy closer to the precision strategy now widely advocated for asthma management. The results of several RCTs document the importance of using the single inhaler triple therapy with ICS, LABA, and LAMA in poorly controlled asthma despite the use of ICS/LABA. The single inhaler triple therapy is likely the most effective therapeutic approach for TTs, regardless of exacerbations.